Is logic a good scientific instrument for doing philosophy? - Suárez-Rivero, David (2021)
In this paper, I offer reasons to show that the goal of Philosophy are arguments, whatever these can be, such as epistemological, political, ethical, aesthetic, ontological, religious, bioethical, metaphysical, among others. I defend that its main objective is to pose, rebuilt, propose, and evaluate arguments using the modern logic. I also present some counter examples, showing that these do not weak my proposal.